THE STATUS OF HAIR MINERALS IN CHRONIC FATIGUE AND DEPRESSED WOMEN - Jeong, Hwee-soo (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Chronic fatigue and depression are common problems in primary care. The status of micronutrients may be related to two conditions. The present study aimed to identify the association of minerals with chronic fatigue and depression. Methods: We conducted a cross-sectional study using medical records of 97 female patients aged 20–64 years old who visited the integrated medical center of a university hospital in Gyeongju, South Korea, from 2013 to 2016. Collected information comprised their scores for the fatigue severity scale, beck depression inventory, and concentrations of mineral in hair samples. Results: The subjects were classified into three groups according to their depression and fatigue scores: 21 patients (21.6%) were free of fatigue and depression, 55 (56.8%)experienced fatigue without depression, and 21 (21.6%) experienced fatigue with depression. The potassium (K) concentration in hair significantly decreased in the groups of fatigue or fatigue with depression compared to the group with free of fatigue and depression (p=0.042). The trend of sodium (Na), K concentration, and Na/magnesium (Mg) ratios in hair gradually decreased with fatigue and depression (p for trend=0.027, 0.037, and 0.03). Conclusion: Chronic fatigue and depression in women are associated with the concentrations of hair minerals, especially Na, K, and Na/Mg ratios.